Computational thinking, porogramming and robotics in basic education: evaluation of an in-service teacher's b-learning experience - Amante, Lúcia (2020)
This paper presents a training program for teachers and the procedures for its evaluation in the domain of computational thinking, programming and robotics in basic education. This training was conducted within the scope of Project KML II - Laboratory of programming and robotics technologies and learning for preschool and primary school (1st CEB) and is expected to contribute for two of the project's main outcomes: conceive a training plan to include in the higher education of educators and teachers of the 1st ECB and the creation of a MOOC for initial and continuous training of these professionals. The training, with 50 hours of total workload, was developed in a blended learning format, including face-to-face and online sessions (25 hours each). The online sessions were organized into synchronous and asynchronous activities, including autonomous working moments, to perform individual activities. The theoretical references that support this work have their origins in the studies on distance education (EaD), namely in the developments provided by the designated 3rd generation of EaD in which computer-mediated communication has allowed the emergence of new pedagogical scenarios giving rise to new training modalities either fully online or in blended learning format. The training evaluation questionnaire aims to explore the key points that determined the organization of the course and aims to evaluate the level of satisfaction and the opinion of the trainees about the different components of the training, as well as gather information that may contribute to the design of new course in a MOOC format. The questionnaire was designed considering the following dimensions: characterization of respondents and previous experience, satisfaction with training, perception of the learning and involvement in training, perception of the practical application of training, criticism and suggestions for improvement. The questionnaire, in the context of this research, will be an essential source of information for the team's decision-making on the appropriate format for the MOOC to be developed in the future and which constitutes one of the project's final objectives with a view to broadening the access of teachers in Portugal to knowledge on the subject under study.